2022
DOI: 10.32322/jhsm.1138691
|View full text |Cite
|
Sign up to set email alerts
|

Examining the long-term effects of COVID-19 on the umbilical cord

Abstract: Introduction: It is known that COVID-19 in pregnancy causes some negative consequences. Although some studies have been conducted on the possible effects of COVID-19 seen in late pregnancy, its effects in the previous trimesters are not clearly known. This study aimed to examine the umbilical cords of pregnant women who did not have COVID-19 and those who had in the second and third trimesters, after delivery using histopathological and immunohistochemical methods. Material and Method: The study include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…patients. 18,19 The main mechanism determining mortality and morbidity in this disease is considered to be the activation of the innate immune system with cytokine storm. 18 TNF-α is involved in many acute inflammatory reactions and its expression is increased during inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…patients. 18,19 The main mechanism determining mortality and morbidity in this disease is considered to be the activation of the innate immune system with cytokine storm. 18 TNF-α is involved in many acute inflammatory reactions and its expression is increased during inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are studies showing histopathologic changes caused by COVID-19 infection on both placenta and umbilical cord [12][13] . Apart from covid-19 infection, diseases such as preeclampsia also cause histologic changes in the placenta 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that especially intervillous thrombosis fibril accumulation was prominent in the basal plaque layer and the distribution of lesions related to the degree of invasive subgroups of structures containing large-scale lacunae was significant 10 . Like placenta previa, preeclampsia and covid-19 infection also cause histologic changes in the placenta and umblical cord [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%